2020
DOI: 10.4103/jfmpc.jfmpc_1512_20
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 antibody serology testing correlate with disease severity? An analytical descriptive retrospective study

Abstract: Aim: To find out if there is any correlation between COVID-19 antibody serological testing and symptom severity. Methods: This study is a case series of 44 consecutive patients confirmed with COVID-19 who are divided into a group of 23 patients with mild disease and a group of 21 patients with severe disease. All 44 samples were confirmed positive SARS-CoV-2. Subsequent recombinant SARS-CoV-2 S1/S2 IgG test was performed for all patients and all patients developed neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Furthermore, Oved et al 14 noted that SARS-CoV-2 Ab titers were significantly correlated to disease severity with a significant trend from asymptomatic to mild to moderate/severe patients. Two other studies 23,24 reported significantly higher titers in patients with moderate/severe COVID-19 comparatively to those with mild disease. This increased humoral response could be due to higher viral loads in severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, Oved et al 14 noted that SARS-CoV-2 Ab titers were significantly correlated to disease severity with a significant trend from asymptomatic to mild to moderate/severe patients. Two other studies 23,24 reported significantly higher titers in patients with moderate/severe COVID-19 comparatively to those with mild disease. This increased humoral response could be due to higher viral loads in severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 85%
“…A spectrum bias occurs when the sample of known infected is not representative of infected individuals in the population under study. This bias is often suspected, as symptomatic individuals are more likely to be detected and therefore recruited to study sensitivity, and are also more likely to have higher antibody levels [13][14][15][16]. In that case, a sensitivity parameter can be estimated in each infected sub-group (symptomatic or asymptomatic).…”
Section: Introductionmentioning
confidence: 99%